Production of sodium metaborate tetrahydrate (NaB(OH)4•2H2O) using ultrasonic irradiation - Yilmaz, Muge Sari; Figen, Aysel Kanturk; Piskin, Sabriye (ELSEVIER, 2012)
Sodium metaborate, a derivative of the borax compound, has a wide range of industrial applications. Recently, it is used as a source of boron in the production of sodium borohydride (NaBH4), which is a medium for hydrogen storage. In the present study, sodium metaborate tetrahydrate (SMT, NaB(OH)(4)center dot 2H(2)O) was produced by the reaction of borax (B) with the sodium hydroxide (SH) solution under ultrasonic irradiation. The effect of the reaction parameters (amount of water. temperature, particle size, and time) on the production of sodium metaborate tetrahydrate was investigated in the present study. It was shown that the reaction parameters (amount of water, temperature, and time) played a significant role in the synthesis of sodium metaborate tetrahydrate. In addition, the concentration of characteristic B-O group in the reaction solution was quantitatively determined by Fourier Transform Infrared Spectroscopy (FTIR). The optimum condition for the production process included 26% water by weight, borax particles of size -250+150 mu m and irradiation time of 60 min at 80 degrees C. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Sodium metaborate tetrahydrate; Production; Ultrasonic irradiation; FTIR; Quantitative analysis; Sodium borohydride; QUANTITATIVE-ANALYSIS; BOROHYDRIDE; Engineering